The impact of road familiarity on the perception of traffic signs – eye tracking case study - Babić, Dario; Babić, Darko; Ščukanec, Anđelko (International Conference “Environmental Engineering”, 2017)
Traffic sign visual information provides road users with the basic instructions regarding route selection, safety at intersections, warnings on physical obstacles on the road and safe route marking. The use of sophisticated eye tracking systems is an efficient way to analyse the influence of traffic signs on drivers’ behaviour. In this paper, the drivers’ perception of traffics signs has been analysed using such a system. The aim of this paper is to determine how the perception of traffic signs changes according to the frequency of driving on a specific route or according to the route familiarity. The results show that the drivers’ perception of traffic signs declines as they get familiar with the route and road conditions. In addition, older drivers having more driving experience perceive fewer signs and elements from the environment because they are often led by their own experience and knowledge, so they do not need the same amount of information as compared to younger drivers.